Transference of metals in the soil‐food chain system: of Caspian Sea sturgeons - V. A. Chaplygin; T. S. Ershova; V. F. Zaitsev (Юг России: экология, развитие, 2019)
Aim. Identification of metal transference characteristics in components of the ecosystem of the north‐western part of the Caspian Sea.   Material and Methods. Sampling was carried out according to generally accepted  methods and the determination of heavy metals was carried out by atomic absorption spectroscopy using an atomic absorption spectrometer with electro‐thermal  atomization MGA‐915 MD.   Results. In studying the migration of trace elements in the trophic chains of the  Caspian Sea sturgeon species it was found that: (a) chromium, manganese and iron  do not accumulate along the trophic chain researched; (b) accumulation of lead and  cobalt above the trophic level occupied by benthic invertebrates did not occur; (c)  cadmium, nickel and copper were accumulated primarily by benthic organisms,  while cadmium and nickel accumulated in the kidneys of Russian and Persian sturgeons and copper accumulated in the liver of both species (d) bioaccumulation of  zinc occurs sequentially in the links: soil‐water‐benthic invertebrates‐benthophage  fish (in Russian and Persian sturgeons in their kidneys, liver and muscles) and (e)  mercury migrates along the links of the food chain, accumulation coefficients increasing progressively in the system: soil‐Didacna mollusc‐benthophage fish (in  Russian and Persian sturgeons in their kidneys, liver and muscles).   Conclusion. The accumulation of heavy metals from water amongst aquatic organisms depends on the properties of the metal, its involvement in biochemical processes, species, biological status and the nature of abiotic living conditions.